Perkembangan Ekstrakurikuler Pencak Silat Siswa SMA Negeri Kabupaten Lebong - Rahmadani, Pitri; Pujianto, Dian; Sihombing, Santun (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2020)
The studyaims to find out how the development of pencak silat extracuricular activities at Lebong Regency High School and the factor that influencer student achievemrnt. This type of research is descriptive qualitative. The research subjects were 64 high school pencak silat extracurricular athletes in Lebong Regency, then collecting research data using questionnaire and interview techniques. Analysis of the data used in this research is data reduction, display, and conclucing drawing. The results of this study showed that the pencak silat extracurricular human resousrces in Lebong Regency were 27% in the poor category, 24%in the poor infrastructure, 33% in  the funding management, in the training method and program 23% in the inadequate category. Thus it can be concluded that the development of pencak silat extracurricular activities in the Lebong Regency High School is in the inadequate category.